Prevalence of non-strabismic binocular vision anomalies and age-related changes in binocular vision among middle-aged and older adults: a systematic review - Chun-Yan Lai; Chang-Kang Luo; Wei Zhao; Jia-Hao Tan; Wen Fu; Hui Ren; Bao-Wen Zhang; Qing-Qing Tan (BMC Ophthalmology)
Abstract Background With the global aging population, binocular vision anomalies in middle-aged and older adults have gained increasing attention. Non-Strabismic Binocular Vision Anomalies (NSBVAs) are particularly prevalent in this population, yet clinical research remains insufficient. To bridge this gap, we conducted a systematic review to evaluate NSBVAs prevalence and subtypes in middle-aged and older adults and analyze age-related changes in binocular vision. The aim was to clarify how aging affects binocular function and inform clinical management. Methods Studies were identified using PubMed, Web of Science and existing reviews, with the search strategy incorporating terms related to binocular vision alterations in middle-aged and older adults (40 years and older). Cross-sectional studies and observational cohort studies investigating binocular vision alterations in this population were included. The study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 statement guidelines. Two independent researchers carried out all study procedures, including literature search, quality assessment using the Critical Appraisal Skills Programme Quality Appraisal Scale, and blinded study selection and data extraction. The main outcomes and measures were the measurement parameters of binocular vision function and the prevalence rates of NSBVAs in middle-aged and older adults. Results Among the eight studies included in this review, all examined binocular vision measures in middle-aged and older adults. Age demonstrates a significant influence on these measures. However, data regarding the prevalence of binocular vision anomalies within this population remain limited. Specifically, only four studies reported the prevalence of specific diagnosed conditions, while an additional two studies documented the prevalence of abnormal binocular vision test results that did not correspond to defined diagnostic criteria. All eight studies were assessed as being of moderate to high methodological quality. Conclusion The existing literature indicates that age significantly influences binocular vision function, with NSBVAs being particularly prevalent among middle-aged and older adults. However, prior studies predominantly focus on the prevalence of abnormal individual test results in this group, while limited data are available regarding actual diagnostic conditions. Establishing normative reference values for binocular vision parameters is therefore essential to determine a more accurate prevalence rate of NSBVAs in this population.